2022
DOI: 10.3390/cancers14174159
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3A/miR-129-2-5p/Rac1 Is an Effector Pathway for SNHG1 to Drive Stem-Cell-like and Invasive Behaviors of Advanced Bladder Cancer Cells

Abstract: The stem-cell-like behavior of cancer cells plays a central role in tumor heterogeneity and invasion and correlates closely with drug resistance and unfavorable clinical outcomes. However, the molecular underpinnings of cancer cell stemness remain incompletely defined. Here, we show that SNHG1, a long non-coding RNA that is over-expressed in ~95% of human muscle-invasive bladder cancers (MIBCs), induces stem-cell-like sphere formation and the invasion of cultured bladder cancer cells by upregulating Rho GTPase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…The latest studies on the functions and mechanisms of SNHGs in BLCA are described below (Table 1). SNHG1, which is located at chromosome 11q12.3, is overexpressed in several types of tumours, including pancreatic, prostate, non-small-cell lung and BLCA [21][22][23][24]. It is widely considered an oncogene that promotes cancer proliferation, migration, invasion and tumorigenesis.…”
Section: The Role Of Snorna In Blcamentioning
confidence: 99%
See 1 more Smart Citation
“…The latest studies on the functions and mechanisms of SNHGs in BLCA are described below (Table 1). SNHG1, which is located at chromosome 11q12.3, is overexpressed in several types of tumours, including pancreatic, prostate, non-small-cell lung and BLCA [21][22][23][24]. It is widely considered an oncogene that promotes cancer proliferation, migration, invasion and tumorigenesis.…”
Section: The Role Of Snorna In Blcamentioning
confidence: 99%
“…A recent study revealed that elevated SNHG1 could interact with the DNA methyltransferase DNMT3A and then bind to and hypermethylate the promoter of miR-129-5p. The low expression of miR-129-5p maintains the stability of Rac1 mRNA, resulting in increased stemness and invasiveness of BLCA cells [22]. Moreover, SNHG1 upregulates the histone methyltransferase EZH2 by direct interaction and functions as a sponge of miR-137-3p.…”
Section: The Role Of Snorna In Blcamentioning
confidence: 99%